Evaluasi Kinerja Angkutan Massal Bus Rapid Transit Pada Koridor Rajabasa - Sukaraja - Muhammad, Nurfadli; Heriyanto, Dwi; Pratomo, Priyo (Universitas Lampung, 2015)
The growing population and the increasing economic growth in the city of Bandar Lampung haveled to expanding geographic mobility within the city. The provision of a mass transit system,therefore, is vastly indispensable for anticipating high traffic densities. This study was trying toexamine whether the operational performance of trans-Bandar Lampung buses, or called “BusRapid Transit” (BRT), has conformed to the existing standards. The results are expected to betaken for consideration by the municipal government when adopting policies to improve BRT’soperational performance and to scale back traffic jams.The study focused only on one corridor, the Rajabasa-Sukaraja corridor, and used the World Bank(1986) standards as the reference. Observations were then made in three days: Monday andThursday to represent workdays, and Sunday to represent days off, with each observation dayspanning from 6.00 a.m. to 6.00 p.m.The results reveal that time headway, 6.29 minutes (on the Rajabasa-Sukaraja corridor), and tripspeed, 25.45 km/h, have met the World Bank’s standards. However, traveled distance, 112.36 kmper vehicle, and load factor, 20.53%, are below the given standards. This low load factor has led tosmall revenue per vehicle, i.e. only Rp346,503.56. Dividing the amount by the operating cost(operating ratio) per vehicle gives us a value of 0.7 (less than 1). In other words, the BRT systemhas been operating at a loss.In the final analysis, it is vital that the municipal government take strategic policies to reduce thenumber of minibuses, or angkot, that operates on the same corridor as the BRT buses’, so thatmore passengers will shift to these BRT buses. The government should also grant subsidiesimmediately to make up for the loss currently being suffered by this BRT.Keyword : BRT, trans-Bandar Lampung bus, Rajabasa, Sukaraja, time headway, load factor.